Clinical development of new prophylactic antimalarial drugs after the 5th Amendment to the Declaration of Helsinki - Geoffrey S Dow; Alan J Magill; Colin Ohrt (Dove Medical Press, 2008)
Geoffrey S Dow, Alan J Magill, Colin OhrtDivision of Experimental Therapeutics, Walter Reed Army Institute of Research, Silver Spring, MD, USAAbstract: Malaria is of continuing concern in nonimmune traveling populations. Traditionally, antimalarial drugs have been developed as agents for dual indications (treatment and prophylaxis). However, since 2000, when the 5th Amendment to the Declaration of Helsinki (DH2000) was adopted, development of new malaria prophylaxis drugs in this manner has ceased. As a consequence, there may not be any new drugs licensed for this indication in the foreseeable future. Major pharmaceutical companies have interpreted DH2000 to mean that the traditional development paradigm may be considered unethical because of doubt over the likelihood of benefit to endemic populations participating in clinical studies, the use of placebo, and the sustainability of post-trial access to study medications. In this article, we explore the basis of these concerns and suggest that the traditional development paradigm remains ethical under certain circumstances. We also consider alternative approaches that may be more attractive to sponsors as they either do not use placebo, or utilize populations in endemic countries who may unambiguously benefit. These approaches represent the way forward in the future, but are at present unproven in clinical practice, and face numerous regulatory, logistical and technical challenges. Consequently, in the short term, we argue that the traditional clinical development paradigm remains the most feasible approach and is ethical and consistent with the spirit of DH2000 under the appropriate circumstances.Keywords: malaria, prophylaxis, treatment, Declaration of Helsinki, DH2000, ethics